Поморье. Сокровищница Русского Севера - Голицына Ирина Анатольевна (История России, 2009)
Экземпляры: ф. 2 (20101125) / Инвентарный номер: 96632 / Цена: 140.00 / Авт.знак: Г 60 / ГРНТИ: 39 / ББК: 26.89(2Рос)